Towards Determining Wall Properties with Bistatic Radar - Elgy, James; Andre, Daniel; Morrow, Ivor L.; Finnis, Mark V. (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.Remote sensing techniques to gather information about building structure and interiors are of significant interest for both military and civilian applications. Radar offers an attractive approach due its long-range, all-weather and non-destructive through-wall sensing nature. Radar however, is affected by the electrical properties of the medium the electromagnetic waves are passing through. For through-wall Synthetic Aperture Radar (SAR), this leads to a defocusing and a distortion of the resultant radar images due to the decrease in velocity and refraction of the radio waves. Compensation for this effect is possible if the properties of the medium are accounted for.This research contributes to the Remote Intelligence of Building Interiors (RIBI) project through use of multistatic measuring geometries and novel signal processing techniques to determine the thickness, refractive index and other electrical properties of walls, remotely, in both laboratory and realistic environments.We present experimental results, gathered at the Cranfield University Antennas and Ground-Based SAR (AGBSAR) laboratory to both validate our simulations and to illustrate the effectiveness of our proposed method as a means of addressing some of the fundamental issues with through-wall radar remote sensing.
Keywords: 'Through-Wall'; 'Bistatic'; 'Synthetic Aperture Radar'; 'DSDS17 poster'; 'DSDS17'; 'Photogrammetry and Remote Sensing'